Sources and Reduction of Noise in Circuits and Systems. Issue 2 (2nd July 2016) - Narayanan, Ram M.
ABSTRACT: This article provides information on sources of different types of noise in circuits and their deleterious effects, and provides recommendations to mitigate their impact on circuits and systems. The effects of noise on circuit and system performance are discussed, followed by the characteristics of noise from electrical and non-electrical sources. Good circuit layout considerations are provided, including grounding, shielding, and filtering.